An Analysis of Arabic Writing Skills (Mahārah al-Kitābah) in Tanmiyat Mahārāt al-Qirā’ah wa al-Kitābah Based on the Reference Framework for Teaching Arabic to Non-Native Speakers (IMTA’) with Multiple Teaching and Assessment Strategies - Lutfhi Kirani, Lintang; Azizah, Miftahul; Ritonga, Arip Rachman (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to analyze Tanmiyat Mahārāt al-Qirā’ah wa al-Kitābah using the IMTA’ Reference Framework for Teaching Arabic to Non-Native Speakers (Development – Instruction – Training). Employing a qualitative descriptive method with a content analysis approach, the research finds that the book fully conforms to the IMTA’ framework. The approach used in this research is qualitative, employing the content analysis methodology. This study utilizes a single instrument, namely documentation, supported by several scholarly references. Based on the collected data, several stages of data analysis were carried out. Based on the analysis, formal writing skills fall under the category of Mustawā al-Tamayyuz (Excellence Level), while non-formal writing skills are categorized under Mustawā al-Tahyiī’ah (Preparation Level). Furthermore, the stages of writing-skill development are situated within cognitive processes and coherence, which correspond to Mustawā al-Kifāyah (Proficiency Level). Furthermore, five stages in the writing process have been analyzed using the IMTA’ framework, and five corresponding strategies for developing writing skills have been identified, all of which align with the principles of the IMTA’ framework.